Implementation of Numeracy Literacy through Economics Learning in Elementary School - Aishalya, Althafia Siti; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Indonesian Journal of Multidiciplinary Research, 2022)
Numeracy literacy is intended so that students can solve practical problems related to numbers in daily life. The purpose of this study was to determine the knowledge that students have about economics learning applied to numeracy literacy. The subjects taken in this study were students of fifth-grade Elementary School, Bandung, Indonesia. The data collection instrument used a pretest-posttest which was made in the Quizizz Application. The results of this study state that the average student still didn’t understand numeracy literacy. Students' understanding of the material for numeracy literacy can be improved by providing economics material via PowerPoint or YouTube which is done online from using the zoom application with educators. The results of the research show that the average post-test score for all of the sample students is 90.6% greater than the average pre-test score of 56.6% so the difference is 34%. Therefore, learning economics can be improving their numeracy literacy students’ skills.